Theoretical Frameworks for Math Fact Fluency - Arnold, Katherine (Journal of the American Academy of Special Education Professionals, 2012)
Recent education statistics indicate persistent low math scores for our nation’s students. This drop in math proficiency includes deficits in basic number sense and automaticity of math facts. The decrease has been recorded across all grade levels with the elementary levels showing the greatest loss (National Center for Education Statistics, 2009). The purpose of this paper is to use Vygotsky’s sociocultural theory as a framework to discuss the benefits of peer assisted drill and practice for math fact fluency. One basic aspect of this theory centers on the contention that cognitive growth and development can be promoted in less capable peers if they are given opportunities to interact with more capable peers (Vygotsky, 1978). In addition, the delivery and effectiveness of computer assisted drill and practice will be discussed within the context of the Information Processing Theory. These theories are based on the assumption that cognitive manipulation of input must precede its release as output (Miller, 2011). The theory is based on a model much like a computer. Through a review of literature and current research, the two methods of math practice will be compared and contrasted.